EFEKTIVITAS PEMANFAATAN SUDUT BACA MENGGUNAKAN BUKU LITERASI BERMUTU DALAM MENINGKATKAN KETERAMPILAN MINAT BACA SISWA KELAS TINGGI (Studi Kasus di UPT SPF SDN 105313 Namo Rumbe Julu) - Sitepu, Fitriani Br; Harahap, Fitri Hariani; Hartati, Sri; Arwana, Ema Rasti; P Wahyuni, Elly; Anshari, Khairil (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the utilization of reading corners with high-quality literacy materials that play an important role in improving upper-grade students’ reading skills and interest at UPT SPF SDN 105313 Namo Rube Julu. Reading corners containing quality literacy materials can create an enjoyable learning environment and encourage students to be more active readers. This research seeks to analyze the effectiveness of reading corners in enhancing students’ reading skills through a quality literacy approach. The study employed a qualitative method with a descriptive case study design. The results show that the use of reading corners with quality literacy books significantly improved students’ reading skills and interest. Before the intervention, only 40% of students had a high interest in reading and actively visited the reading corner. After the implementation of reading corners with engaging reading materials and teacher guidance, the percentage increased to 85%. Additionally, students’ reading skill test results improved, with those in the “good” and “very good” categories rising from 45% to 82%. This improvement was influenced by factors such as providing books suited to students’ developmental levels, creating a comfortable reading environment, and teacher encouragement for regular reading. Observations also revealed more frequent book discussions, indicating improved text comprehension. The study concludes that well-managed reading corners supported by quality literacy materials effectively enhance students’ reading interest and skills.